Avaliação da vitalidade de cordeiros nascidos de partos eutócicos e cesarianas - Bovino, Fernanda [UNESP]; de Camargo, Diogo G. [UNESP]; de Araújo, Marcelo A. [UNESP]; Costa, Felipe de P. [UNESP]; dos Santos, Paulo Sérgio P. [UNESP]; Mendes, Luiz Claudio N. [UNESP]; Peiró, Juliana R. [UNESP]; Feitosa, Francisco Leydson F. [UNESP] (FapUNIFESP (SciELO), 2014)
The aim of this study was to evaluate vitality of lambs born by normal delivery and cesarean section, during 48 hours of life, by means of APGAR score, behavior and vital parameters. The first group was formed with lambs born by normal delivery (NORMAL) and the other two groups were formed with lambs born by cesarean sections, but with two different anesthetic protocols, one used inhalation anesthesia (INAL) and the other total intravenous anesthesia (TIVA). Lambs in the NORMAL group obtained higher pontuation in Apgar score. At birth and 15 minutes, 93.75[%] of lambs NORMAL group obtained maximum score (7-8), while no lambs born by cesarean section obtained this score at birth. At 15 minutes, 25.00[%] of the lambs INAL group received the same score. The heart rate remained virtually unchanged for both groups, with a tendency to decrease values, at 24 hours for group TIVA animals. The respiratory rate at birth for the animals delivered by cesarean section (26±25 bpm, INAL; 5±5 bpm, TIVA) was significantly lower than for the ones of the normal delivery. Nevertheless, that value at 60 minutes was found quite close. A tendency for decreasing temperature values was verified until the 15 minutes in all groups, lasting until 60 minutes in animals in the TIVA group. Lambs born by c-section have lower vitality than lambs born by normal delivery.
Evaluation of vitality in lambs born by normal delivery and cesarean section